Design of compact dual-band patch antenna loaded with D-shaped complementary split ring resonator. Issue 16 (2nd November 2019) - Singh, Ghanshyam; Kanaujia, Binod Kumar; Pandey, Vijay K.; Gangwar, Deepak; Kumar, Sachin
ABSTRACT: In this paper, an inset-fed dual-band patch antenna with truncated corners is presented. The ground plane of the antenna is loaded with D-shaped complementary split ring resonator (D-CSRR) structures to obtain dual-band resonance and size miniaturization. The overall electrical size of the antenna is 0.29 λ 0  × 0.25 λ 0 and patch size is 0.14 λ 0  × 0.13 λ 0, where λ 0 is evaluated at the lowest resonating frequency. The proposed planar antenna is low profile and does not need a dual feed or any external feeding mechanism for obtaining circular polarization. A size reduction of 66% is achieved as compared to the conventional patch antenna. The newly designed D-CSRR results in better miniaturization factor making proposed antenna suitable for modern wireless applications. The prototype of the antenna is fabricated and experimental findings are compared with electromagnetic and analytical results.